(untitled) (Geographical Journal of Nepal, 2018)
Livelihood strategy varies from place to place. People living in certain place have a diverse strategy over time. This study attempts to analyze the sources of livelihood, livelihood strategies of different communities and their adaptive strategies in Melamchi Valley. The livelihood patterns and the strategies have been dealt on the basis of community. This study is based on primary data that are collected using household questionnaire, focus group discussion and key informant interview. A set of standardized questionnaire, observation sheet, and checklist were used for information collection. The finding of the study portrays that paddy is the major crop cultivated by Brahmin/Kshetri communities whereas millet and maize are the principal crops cultivated by Tamang community. People of this area are attracted towards cash generating activities than the subsistence agriculture farming in the present days. The people of market center are motivated towards trade and business whereas the people of remote area have dependence on remittance. The trend of foreign migration for earning livelihood is high among the rural settlements. Similarly, earning from wage labor in the informal sectors has become important source of livelihood in Melamchi Valley. The Geographical Journal of Nepal Vol. 11: 113-126, 2018